Endocannabinoid Modulation of Dopaminergic Motor Circuits - Morera-Herreras, Teresa; Miguelez, Cristina; Aristieta, Asier; Ruiz-Ortega, José Ángel; Ugedo, Luisa (Frontiers in Pharmacology, 2012)
There is substantial evidence supporting a role for the endocannabinoid system as a modulator of the dopaminergic activity in the basal ganglia, a forebrain system that integrates cortical information to coordinate motor activity regulating signals. In fact, the administration of plant-derived, synthetic or endogenous cannabinoids produces several effects on motor function. These effects are mediated primarily through the CB1 receptors that are densely located in the dopamine-enriched basal ganglia networks, suggesting that the motor effects of endocannabinoids are due, at least in part, to modulation of dopaminergic transmission. On the other hand, there are profound changes in CB1 receptor cannabinoid signaling in the basal ganglia circuits after dopamine depletion (as happens in Parkinson´s disease) and following L-DOPA replacement therapy. Therefore, it has been suggested that endocannabinoid system modulation may constitute an important component in new therapeutic approaches to the treatment of motor disturbances. In this article we will review studies supporting the endocannabinoid modulation of dopaminergic motor circuits.